Przegląd wybranych metod rehabilitacji kończyny górnej u pacjentów po przebytym udarze niedokrwiennym mózgu = A review of selected methods for the rehabilitation of the upper extremity in patients after undergone brain ischemic stroke - Joanna Siminska; Katarzyna Pietkun; Piotr Porzych; Iwona Głowacka; Anna Świątkowska; Karol Ogurkowski; Sebastian Grzyb; Krystyna Nowacka; Wojciech Beuth (Kazimierz Wielki University, 2016)
Siminska Joanna, Pietkun Katarzyna, Porzych Piotr, Głowacka Iwona, Świątkowska Anna, Ogurkowski Karol, Grzyb Sebastian, Nowacka Krystyna, Beuth Wojciech. Przegląd wybranych metod rehabilitacji kończyny górnej u pacjentów po przebytym udarze niedokrwiennym mózgu = A review of selected methods for the rehabilitation of the upper extremity in patients after undergone brain ischemic stroke. Journal of Education, Health and Sport. 2016;6(4):240-248. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50155 http://ojs.ukw.edu.pl/index.php/johs/article/view/3466   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016.     PRZEGLĄD WYBRANYCH METOD REHABILITACJI KOŃCZYNY GÓRNEJ U PACJENTÓW PO PRZEBYTYM UDARZE NIEDOKRWIENNYM MÓZGU A review of selected methods for the rehabilitation of the upper extremity in patients after undergone brain ischemic stroke   Siminska Joanna1, Pietkun Katarzyna1,2, Porzych Piotr1, Głowacka Iwona1, Świątkowska Anna1, Ogurkowski Karol1, Grzyb Sebastian3, Nowacka Krystyna1, Beuth Wojciech4   1Katedra i Klinika Rehabilitacji CM UMK Bydgoszcz 2Katedry Kosmetologii i Dermatologii Estetycznej CM UMK Bydgoszcz 3Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej CM UMK Bydgoszcz 4Oddział Neurochirurgii, Wojewódzki Szpital Specjalistyczny, Włocławek   Słowa kluczowe: udar niedokrwienny mózgu. Keywords: ischemic stroke.     Streszczenie   Analizując dane statystyczne uważa się, że udary mózgu stanowią około 15% wszystkich zgonów na świecie. W Polsce na udar mózgu zapada około 70 tysięcy osób rocznie , spośród których w okresie pierwszego miesiąca umiera około 20%, kolejne 10-25% pacjentów odzyskuje pełną samodzielność, u 40% chorych pozostaje umiarkowana niepełnosprawność, zaś około 15-30%  osób wymaga stałej pomocy osób drugich. Dlatego tak niezwykle istotnym faktem staje się wczesne wdrążenie właściwych algorytmów postępowania procedur rehabilitacji. Wiadomo, że optymalnym okresem powrotu i poprawy funkcji, w tym wykonywania czynności samoobsługowych, są pierwsze 3 miesiące od wystąpienia incydentu udaru mózgu. W tym okresie należy odpowiednio zaplanować i zastosować możliwie najefektywniejsze metody leczenia i usprawniania, co pozwala na poprawę jakości życia jak i podniesienie możliwości wykonywania czynności w zakresie samoobsługi tych chorych.   Abstract   Analysing statistical data, it is considered that strokes account for approximately 15% of all deaths in the world. In Poland the stroke falls approximately 70 thousand people per year, of which during the first month dies around 20%, 10-25% of patients recover full autonomy in 40% of patients remains a moderate disability, while about 15-30% of people requires constant assistance of another person. Why it is so extremely important fact becomes early implementation of the relevant algorithms conduct rehabilitation procedures. It is known that the optimal period of return and improved features, including self-service operations, are the first 3 months of the occurrence of an incident of stroke. During this period, please plan accordingly and apply as soon as possible the most effective methods of treatment and improve, allowing you to improve the quality of life and raise the possibility of performing self-service operations of these patients.